The Fundamental Stellar Parameters of FGK Stars in the SEEDS Survey Norman, OK 73071, USA - Rich, Evan A.; Wisniewski, John P.; McElwain, Michael W.; Hashimoto, Jun; Kudo, Tomoyuki; Kusakabe, Nobuhiko; Okamoto, Yoshiko K.; Abe, Lyu; Akiyama, Eiji; Brandner, Wolfgang; Brandt, Timothy D.; Cargile, Phillip; et al. (Monthly notices of the Royal Astronomical Society, 2017)
Large exoplanet surveys have successfully detected thousands of exoplanets to-date. Utilizing these detections and non-detections to constrain our understanding of the formation and evolution of planetary systems also requires a detailed understanding of the basic properties of their host stars. We have determined the basic stellar properties of F, K and G stars in the Strategic Exploration of Exoplanets and Disks with Subaru (SEEDS) survey from Echelle spectra taken at the Apache Point Observatory's 3.5m telescope. Using ROBOSPECT to extract line equivalent widths and Temperature Gravity microtrubulent Velocity ITerations to calculate the fundamental parameters, we have computed T(sub eff), log(g), v(sub t), [Fe/H], chromospheric activity and the age for our sample. Our methodology was calibrated against previously published results for a portion of our sample. The distribution of [Fe/H] in our sample is consistent with that typical of the Solar neighbourhood. Additionally, we find the ages of most of our sample are less than 500 Myr, but note that we cannot determine robust ages from significantly older stars via chromospheric activity age indicators. The future meta-analysis of the frequency of wide stellar and sub-stellar companions imaged via the SEEDS survey will utilize our results to constrain the occurrence of detected comoving companions with the properties of their host stars.